PENINGKATAN AKTIVITAS DAN HASIL BELAJAR FISIKA MELALUI PEMBELAJARAN FISIKA GASING PADA SISWA KELAS X-2 SMA NEGERI 1 PINANGSORI TAHUN PELAJARAN 2016/2017 - Muhammad Ali (Universitas Muhammadiyah Tapanuli Selatan, 2018)
Research action class it aims to find out if a top physics learning can improve student learning outcomes and activities. The research consists of two cycles are performed in class X-2 SMA Negeri 1 Pinangsori Central Tapanuli Regency who numbered 33 students. The characteristics of this class have a liveliness and low learning outcomes than classroom X others. Indicators of success for the liveliness of the students at least 75%, and indicators of the results of the study classical at least 85% of the number of students who take the test. During the research showed an increase in the activities and achievements of student learning of the cycle I to cycle II. On cycle I nthe average ilai psychomotor students end of the cycle I of 75.85 became 79.26 end cycle II, the affective value of scientific attitude on cycle I with an average of 78.03 and rose to 80.74 on cycle II. Analysis of the cognitive learning of students obtained through exam results per cycle is done per cycle. Improvement of cognitive learning results seen from the average value obtained before students cycle 65 ketuntasan with 31%, end of cycle I average of 73.52 with ketuntasan 6 3.64 % and the end of sklus II becomes 78, 1 8 with ketuntasan 87.88 %. From the results of the research, it can be concluded that the application of learning physics top can increase the activity and results of the study physics in grade students X-2 SMA Negeri 1 Pinangsori. Keywords: activity, the results of the study and a top Physics.